Increased salivary aldehyde dehydrogenase 1 in non-reticular oral lichen planus - Arash Mansourian; Najmeh Shanbehzadeh; Seyed Javad Kia; Mahdieh-Sadat Moosavi (Sociedade Brasileira de Dermatologia, 2017)
Abstract: Background: Oral lichen planus is a potentially malignant disorder. One of the malignant transformation markers is cancer stem cells. One of the proposed marker for the detection of cancer stem cells's in head and neck cancer is aldehyde dehydrogenase. Recently it is shown that aldehyde dehydrogenase 1 expression in tissue samples is associated with oral lichen planus malignant transformation. Objective: This study evaluates salivary aldehyde dehydrogenase 1 in oral lichen planus. Method: Thirty patients and 30 age and sex-matched healthy volunteers were recruited. Oral lichen planus was diagnosed based on the modified World Health Organization criteria. Subjects in the case group were divided into reticular and non-reticular forms. Unstimulated salivary samples were collected at 10-12 AM. Saliva concentrations of aldehyde dehydrogenase 1 were measured by ELISA. Results: The differences between aldehyde dehydrogenase levels in the oral lichen planus group compared with the control group were not significant but aldehyde dehydrogenase in non-reticular oral lichen planus was significantly higher than that of the reticular form. Limitations of the study: This is a cross-sectional study, thus longitudinal studies in oral lichen planus may present similar or different results. Conclusions: The mechanism of malignant transformation in oral lichen planus is not defined. Previous analyses revealed that the aldehyde dehydrogenase 1 expression is significantly correlated with increased risk of transformation. This finding is consistent with our results because in the erosive and ulcerative forms of oral lichen planus, which have an increased risk of transformation, salivary aldehyde dehydrogenase 1 was overexpressed. A higher salivary aldehyde dehydrogenase level in non-reticular oral lichen planus can be a defensive mechanism against higher oxidative stress in these groups. Aldehyde dehydrogenase may be one of the malignant transformation markers in oral lichen planus. Further studies are needed for introducing aldehyde dehydrogenase as a prognostic indicator in certain lesions.